TEST ANALGESIC ACTIVITY OF 70% ETHANOL EXTRACT OF STARFRUIT LEAVES (Averrhoa bilimbi L.) ON MALE MICE WITH WRITHING TEST METHOD - Manar Syathotho; Wima anggitasari; Gumiarti (LPPM Universitas dr. Soebandi, 2024)
ABSTRACT Introduction: Analgesics are drugs commonly used to reduce or eliminate pain without losing consciousness. Several chemical compounds such as alkaloids, tannins, flavonoids and saponins contained in starfruit leaves have a therapeutic effect in reducing pain (analgesics by inhibiting the cyclooxygenase enzyme in the process of forming prostaglandins. The aim of this research is to determine the analgesic activity of the 70% ethanol extract of starfruit leaves wuluh (averrhoa bilimbi L.) in male mice using the writhing test method. Method: The research was experimental with the writhing test method using experimental mice by observing the writhing of the mice after giving acetic acid induction. Divided into 5 treatment groups, namely positive control paracetamol 65 mg /kgBW, negative control CMC Na 0.5%, group of 70% ethanol extract of starfruit leaves, doses of 100, 300 and 500 mg/kgBW. Results: The results of the study showed that the 70% ethanol extract of starfruit leaves contains chemical compounds, flavonoids, alkaloids, tannins and saponins. The average number of writhing results for CMC Na was 123.6 ± 16,920, paracetamol was 46.6 ± 13,631, and 70% ethanol extract of starfruit leaves at a dose of 100 mg/kgBW was 85.8 ± 18,240, 300 mg /kgBW is 67.2 ± 16,574, and 500 mg/kgBW is 52.6 ± 16,742. Conclusion: Analysis of differences in the number of writhes using the LSD post hoc test, namely doses of 300 mg/kg BW and 500 mg/kg BW, has a significant difference with the CMC Na negative control group and does not have a significant difference with the paracetamol positive control group which shows that this dose is comparable to paracetamol of 65 mg/kgBB as an analgesic. Keywords:Ethanol Extract 70% Starfruit Leaves (averrhoa bilimbi L.), Analgesic, Mice